2019
DOI: 10.1074/jbc.ra118.005682
|View full text |Cite|
|
Sign up to set email alerts
|

Nonconventional glucagon and GLP-1 receptor agonist and antagonist interplay at the GLP-1 receptor revealed in high-throughput FRET assays for cAMP

Abstract: Edited by Jeffrey E. Pessin G protein-coupled receptors (GPCRs) for glucagon (GluR) and glucagon-like peptide-1 (GLP-1R) are normally considered to be highly selective for glucagon and GLP-1, respectively. However, glucagon secreted from pancreatic ␣-cells may accumulate at high concentrations to exert promiscuous effects at the ␤-cell GLP-1R, as may occur in the volume-restricted microenvironment of the islets of Langerhans. Furthermore, systemic administration of GluR or GLP-1R agonists and antagonists at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 79 publications
0
34
0
1
Order By: Relevance
“…Similarly, the inhibitory effect GLP1 induced on ASC proliferation was reversible in the presence of GI. Since each antagonist has been demonstrated to be selective and specific for its respective receptor (Chepurny et al 2019), with no cross-activity, these findings suggest that both receptors are necessary for mediating both glucagon and GLP-1 in ASCs, independently of the ligand. This conclusion is further supported by the absence of any synergistic effects in the block of proliferation obtained when glucagon and native GLP-1 were simultaneously administered to ASCs.…”
Section: Figurementioning
confidence: 83%
See 2 more Smart Citations
“…Similarly, the inhibitory effect GLP1 induced on ASC proliferation was reversible in the presence of GI. Since each antagonist has been demonstrated to be selective and specific for its respective receptor (Chepurny et al 2019), with no cross-activity, these findings suggest that both receptors are necessary for mediating both glucagon and GLP-1 in ASCs, independently of the ligand. This conclusion is further supported by the absence of any synergistic effects in the block of proliferation obtained when glucagon and native GLP-1 were simultaneously administered to ASCs.…”
Section: Figurementioning
confidence: 83%
“…An inhibitory effect similar to that observed with liraglutide had been observed with the cleaved GLP-1 form, GLP-1(9-36), which displays a reduced binding ability to the classical receptor. In order to better clarify the role of GLP-1R and GCGR in mediating the similar effects observed with GLP-1RAs and glucagon in ASCs, we used the specific glucagon receptor antagonist, des-His1-[Glu9]-glucagon(1-29) (GI) (Unson et al 1987, Post et al 1993, Chepurny et al 2019, along with the antagonist of GLP-1R exendin 9-39 (EX). When cell count experiments were repeated in the presence of glucagon alone or in combination with GI (10 nM) or EX (10 nM), the inhibitory effect exerted by glucagon on ASC proliferation was significantly reverted not only by GI (86, 103, 97% for 24, 48, 72-h treatment, respectively), but also by EX (88, 96, 91% for 24, 48, 72-h treatment, respectively), Fig.…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst a significant component of their overall metabolic effect depends on GCGR-mediated increases in energy expenditure to increase weight loss [85,86], recent studies highlight an important role for intra-islet GCG signaling in supporting insulin release [46]. This carries a caveat that the glucagon contribution to insulin secretion probably arises jointly from action at GCGR and GLP-1R, as glucagon is in fact a low affinity agonist at both human [87,88] and mouse GLP-1Rs [46]. Indeed, the cAMP-stimulating and insulinotropic effects of glucagon can be partially blocked by the GLP-1R antagonist exendin(9-39) in mice and in INS-1 832/3 rat beta cells [46,88].…”
Section: Dual and Triple Incretin Peptides -"Twincretins" And "Tricrementioning
confidence: 99%
“…This carries a caveat that the glucagon contribution to insulin secretion probably arises jointly from action at GCGR and GLP-1R, as glucagon is in fact a low affinity agonist at both human [87,88] and mouse GLP-1Rs [46]. Indeed, the cAMP-stimulating and insulinotropic effects of glucagon can be partially blocked by the GLP-1R antagonist exendin(9-39) in mice and in INS-1 832/3 rat beta cells [46,88]. However, data presented in the same studies using gcg -/islets and the orthosteric GCGR antagonist des-his 1 glu 9 -glucagon demonstrated that intact GCGR signaling is required for full glucagon action on beta cells.…”
Section: Dual and Triple Incretin Peptides -"Twincretins" And "Tricrementioning
confidence: 99%